PENGARUH DISIPLIN PEGAWAI TERHADAP PELAYANAN ANGGOTA DPRD KABUPATEN KUTAI TIMUR DI KOMISI D - Muntiatun, Muntiatun (PREDIKSI, 2016)
This study aims to find the effect of employee discipline to service of legislators in the East Kutai Regency of Commission D, therefore the researchers formulated the hypothesis